Ternary chalcogenide LiInSe2: A promising high-performance anode material for lithium ion batteries. (10th October 2019) - Jia, Ning; Zhang, Mengqi; Li, Bo; Li, Chuanchuan; Liu, Yangyang; Zhang, Yupeng; Yu, Tongtong; Liu, Yang; Cui, Deliang; Tao, Xutang
Abstract: Ternary chalcogenides have drawn intense interest as promising alternative anode materials for Li-storage systems benefiting from their high specific capacity. Herein, the electrochemical performance of a new ternary chalcogenide LiInSe2 used for lithium ion anode has been reported for the first time. Furthermore, in view of carbon-coating treatment, the optimized anode LiInSe2 @C for Li-ion batteries exhibits enhanced capacitive behavior and high rate capability. LiInSe2 @C presents a high reversible capacity of 409.1 mA h g −1 at 100 mA g −1 and a reversible capacity of 270 mA h g −1 after 1000 cycles at 1000 mA g −1 . Further analyses evidence that the outstanding rate performance stems from fast electrochemical kinetics, enhanced by the pseudocapacitive effect and improved electronic/ionic conductivity. These results elucidate the attractive lithium storage performance of LiInSe2 compound, and would offer a practical polestar to explore novel ternary chalcogenide for energy storage.